Peningkatan Pemahaman Osteoporosis pada Wanita di Kelurahan Kereng Bangkirai Kota Palangka Raya - Toemon, Angeline Novia; Carmelita, Austin Bertilova; Turnip, Oktaviani Naulita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Osteoporosis is a disease characterised by a decrease in bone density, leading to the risk of fractures, especially in the elderly and post-menopausal women. Although it can be prevented and managed, many people are not aware of the importance of prevention and early detection of osteoporosis. This community service activity aims to increase community understanding and knowledge related to osteoporosis, as well as provide information on the prevention and management of the disease. This activity was carried out in Kereng Bangkirai village, involving people from various age groups, especially the elderly and post-menopausal women. Activities included counselling on the causes, symptoms, and prevention of osteoporosis, light exercise, and physical examination to detect osteoporosis risk. Evaluation showed a significant increase in participants' knowledge about osteoporosis after participating in this activity. Overall, this activity showed high enthusiasm for the material presented and triggered participants to lead a healthy lifestyle to prevent osteoporosis. This activity has a positive impact in increasing public awareness of the importance of maintaining bone health, and is expected to be held on an ongoing basis to reach more individuals, especially those at high risk.